101 Best family card games - Sheinwold, Alfred (New Delhi : Goodwill publishing house, 1992)
A nicely organized book chockablock with games that can be enjoyed by...a variety of ages....Begins with games that children as young as five can play with their parents, then...a number of more complicated games that older children can easily play on their own...a great assortment...clearly written and easy enough for many children to read on their own. Great for the parenting shelf or pull the book out for kids on rainy or snowy days."
This book offers a collection of 101 card games suitable for families, ranging from simple games for young children to more complex ones for older players. It provides clear instructions and illustrations to make learning and playing easy for all ages. Location: 3A
Keywords: Games book